STUDI DESKRIPTIF KUALIFIKASI PETUGAS CODER DAN KEAKURATAN KODE DIAGNOSIS RAWAT JALAN BERDASARKAN ICD-10 DI PUSKESMAS GEMPOL - Nova Dyawati; M. Malik Ibrahim; Ika Puspita Sari (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
Coding inaccuracies in Indonesia still often occur in first-level health facilities, one of which is Gempol Health Center. Of the 30 diagnostic codes, 70% of the codes were inaccurate and 30% of the codes were accurate. Inaccuracies in diagnostic codes may be caused by inappropriate qualifications. The purpose of this study is to describe the qualifications of the coder officers and the accuracy of the outpatient diagnostic code based on ICD-10. The type of research is quantitative descriptive. The subject population, namely all outpatient diagnosis coder officers and the object population, were documents coded by officers in March - April 2022. The sample in this study consisted of 7 coders and 245 files with consecutive sampling technique. The results show that the coder qualifications at Gempol Health Center with the inappropriate coder qualifications are 85.7%, and the appropriate coder qualifications are 14.3%. As well as the accuracy of the outpatient diagnosis code at Gempol Health Center from 245 documents, the results obtained were 63.7% inaccurate codes and 36.3% accurate diagnosis codes. Based on the results of the study, it can be concluded that the qualifications of officers and the accuracy of the diagnosis code are quite low.